2016
DOI: 10.3892/etm.2016.3683
|View full text |Cite
|
Sign up to set email alerts
|

Hypersplenism: History and current status

Abstract: Hypersplenism is a common disorder characterized by an enlarged spleen which causes rapid and premature destruction of blood cells. This review summarizes the history of hypersplenism, discuss its classification and pathogenesis, and examines its diagnosis and treatment options. We performed a comprehensive literature search using PubMed, Web of Knowledge and the China National Knowledge Infrastructure (CNKI) database, reviewed hypersplenism-related articles and summarized the major findings. According to its … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
69
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(76 citation statements)
references
References 45 publications
(48 reference statements)
2
69
0
1
Order By: Relevance
“…Hypersplenism is related to spleen size and phagocytic capacity of splenic macrophages. 34 A larger spleen size, which indicates more blood cells stored, and a higher phagocytic capacity of splenic macrophages would result in lower peripheral blood cell counts, and thus a more obvious increase in peripheral blood cell counts after splenectomy. In 15.9% (62/390) of patient-times with peripheral cytopenia, the blood cells counts increased but they did not reach normal, indicating that in addition to hypersplenism other factors were involved.…”
Section: Discussionmentioning
confidence: 99%
“…Hypersplenism is related to spleen size and phagocytic capacity of splenic macrophages. 34 A larger spleen size, which indicates more blood cells stored, and a higher phagocytic capacity of splenic macrophages would result in lower peripheral blood cell counts, and thus a more obvious increase in peripheral blood cell counts after splenectomy. In 15.9% (62/390) of patient-times with peripheral cytopenia, the blood cells counts increased but they did not reach normal, indicating that in addition to hypersplenism other factors were involved.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, we believe the specific decreases in B and T cells in circulation in MPKCδKO/ ApoE −/− mice were mainly due to the function of splenomegaly, which is known to increase the uptake and clearance of circulating blood cells, likely due to increased monocytes or macrophages in the red pulp of the spleen to cause increased retention of all cell types, even platelets. In multiple studies have shown the surgical removal of the enlarged spleen will rapidly return the circulatory cells to normal levels 39 . It is commonly found that bone marrow progenitor cells of these circulatory cells are not abnormal unless the basic pathogenesis of the disease also affected those bone marrow stem cells, such as those involved in autoimmune diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Compensatory bone marrow hyperplasia is also observed (Lv et al . ). Hypersplenism can generally be classified into either primary or secondary hypersplenism.…”
Section: Discussionmentioning
confidence: 97%
“…Mechanisms causing hypersplenism include retention of blood cells within the spleen, phagocytosis and autoimmunity (Lv et al . ). To the authors’ knowledge, hypersplenism has not been described in horses, but should be considered in clinical cases of pancytopenia in which other causes are eliminated.…”
Section: Introductionmentioning
confidence: 97%